Unraveling metabolite profile variations among resistance and susceptible shallot genotypes related to anthracnose (Colletotrichum gloeosporioides) - RIZKI ABI AMRULLAH; AWANG MAHARIJAYA; AGUS PURWITO; SURYO WIYONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Amrullah RA, Maharijaya A, Purwito A, Wiyono S. 2023. Unraveling metabolite profile variations among resistance and susceptible shallot genotypes related to anthracnose (Colletotrichum gloeosporioides). Biodiversitas 24: 5113-5122.This study used a metabolomics approach to reveal the shallot metabolite profile under anthracnose disease conditions through GC-MS analysis. The aim of this study was to obtain candidate metabolite markers that differentiate shallot genotypes resistant to anthracnose. The results of non-targeted metabolite analysis with GC-MS revealed a shallot metabolite profiles of 54 compounds. The principal component analysis (PCA) model was conducted for reliable and accurate discrimination between uninoculated and inoculated genotypes. Four metabolites were revealed as putative biomarkers of Colletotrichum gloeosporioides Penz. infection, namely linoleic ethyl ester, squalene, octadecanoic acid, and nonacosane. At least some putative biomarkers were applicable for early resistance genotype detection in shallot. These metabolites may help characterize pathogen infection and plant defense responses. This study confirmed metabolomics as a tool to develop a strategy to clarify the mechanism of plant-pathogen interaction. Furthermore, the data presented may be helpful to developing a new method for detecting shallot, that may be resistant to anthracnose caused by C. gloeosporioides.